Interaksi Sosial Antar Kelompok Etnik (Studi Kasus di Kelurahan Tambak Sari, Kecamatan Jambi Selatan, Kota Jambi) (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
This research aims at describing intergroups-social interaction of the 4 (four) biggest ethnic groups in Kelurahan Tambak Sari, Kecamatan Jambi Selatan, Kota Jambi. Fourth groups of ethnics are Malay, Minangkabau, Jawa and Batak. The research method is based on qualitative approach. The research findings show that there are ethnic groups migration to Jambi province. Their migration to Jambi are of economics motive. There are social prejudices as results of low association among the different ethnic groups. Nevertheless, there is no negative social prejudice by same religion. Its means that the ethnic groups which have the same religion can be goodfriend or can forget bad identity of other groups, and integroted to Indonesian society.